Teknik Relaksasi Nafas Dalam Efektif Menurunkan Tingkat Stres pada Lansia - Asda, Patria; Anida, Anida; Sholiqah, Anis Yuli (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2023)
The percentage of theelderly population in Indonesia is currently increasing, including the percentageofelderly people in the province of the Special Region of Yogyakarta, which increasedin 2020 to 14.67% from 12.88% in 2010.This condition shows that Indonesia is entering theera of ageing population, wherea region or country is experiencing an increase caused by increasing life expectancy. People with old age faces many health problems that need to be handled properly. Individuals who enter the elderly period will experience a decrease in body resistance and experience various degenerative diseases. The elderly become easy to experience mental problems, namely stres. This stresful condition continues to occur in the elderly and is not overcome as soon as possible, it will have an impact on the psyche of the elderly. One way that can be applied to reduce the stres level of the elderly is a deep breath relaxation technique. This study aims to determine the effectiveness of deep breath relaxation techniques on the stres level of the elderly. This research design was quasi experimental study with one group pre-post test design. The population was elderly people and sample of 25 people was taken using purposive sampling techniques. Instrument to measure pre and post intervention stres levels using DASS questionnaire 14 items specific to stres levels. Deep breath relaxation intervention is given to elderly with reference to standar operating procedure. The collected data were analyzed with the Wilcoxon Statistical Test. The results showed that there were differences in stres levels before and after administration (p value= 0,0000,005). Conclusion of this research that deep breath relaxation techniques are effective for lowering stres levels in the elderly.